Veronā ke do šarīfzāde : yih Angrezī kitāb Ṭels frām Sikspīr kī majmūʿah-i afsānah-i dilpaẕīr ... - Shakespeare, William (Naval Kišor, 1890)
Urdu prose adaptation of William Shakespeare's Two Gentlemen of Verona